Respuesta :
Equation 1) y = x² + 10x + 11
Equation 2) y = x² + x - 7
Subtract equations from one another.
9x = 18
Divide both sides by 9.
x = 2
Plug in 2 for x in the first equation.
y = x² + 10x + 11
y = 2² + 10(2) + 11
Simplify.
y = 4 + 20 + 11
y = 35
Plug in 35 for y and 2 for x in the first equation to check your work.
y = x² + 10x + 11
35 = 2² + 10(2) + 11
35 = 4 + 20 + 11
35 = 24 + 11
35 = 35
So, we know that our answer is correct! :))
x = 2, y = 35
Equation 2) y = x² + x - 7
Subtract equations from one another.
9x = 18
Divide both sides by 9.
x = 2
Plug in 2 for x in the first equation.
y = x² + 10x + 11
y = 2² + 10(2) + 11
Simplify.
y = 4 + 20 + 11
y = 35
Plug in 35 for y and 2 for x in the first equation to check your work.
y = x² + 10x + 11
35 = 2² + 10(2) + 11
35 = 4 + 20 + 11
35 = 24 + 11
35 = 35
So, we know that our answer is correct! :))
x = 2, y = 35
Answer:
It should be (-2,-5)
Step-by-step explanation:
We could easily check the answer by subbing in x and y with the answer
y=x^2+10x+11
-5=-2^2+10(-2)+11
-5=4-20+11
-5=5
y=x2+x-7
-5=(-2)^2+-2-7
-5=-5
Therefore it should be A, (-2,-5)